Analisis Harga Pokok Produksi Di PT. Pratama Abadi Industri - Dede Sulaeman; Idang Nurodin; Acep Suherman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the cost of production applied by the company PT. Industrial Immortal Pratama. The research method used in this research is using qualitative research methods. The population and sample in this study are based on social issues that exist in the company PT. Pratama Abadi Industri using data collection techniques in the form of library research and in the form of field research with observations, interviews and documentation. The results of the analysis show that the process of the cost of production of PT. Pratama Abadi Industri has not fully used the existing theory, but the process of determining the cost of production of PT. Pratama Abadi Industri is considered normal because the company makes a reserve fee of 2%. Keywords: Cost Of Goods Sold, Company, PT. Pratama Abadi Industri